2012
DOI: 10.1063/1.4714727
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial growth of oxide nanoscaffolds and its influence in osteoblast cell adhesion

Abstract: We report a novel method for high-throughput investigations on cell-material interactions based on metal oxide nanoscaffolds. These scaffolds possess a continuous gradient of various titanium alloys allowing the compositional and morphological variation that could substantially improve the formation of an osseointegrative interface with bone. The model nanoscaffold has been fabricated on commercially pure titanium (cp-Ti) substrate with a compositional gradients of tin (Sn), chromium (Cr), and niobium (Nb) dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Stellate cells can firmly attach, spread and eventually proliferate well on the matrix, whereas bipolar spindle cells are still migrating to locate sites for subsequent spreading and proliferation. 55 Thus, it is reasonable to conclude that the addition of silicate sol could promote the proliferation of MG-63 cells. The cell morphology changes and improved proliferation capacity can be mainly ascribed to two reasons: the calcium-dependent regulation and the highly enhanced hydrophilicity provided by the presence of the inorganic phase.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Stellate cells can firmly attach, spread and eventually proliferate well on the matrix, whereas bipolar spindle cells are still migrating to locate sites for subsequent spreading and proliferation. 55 Thus, it is reasonable to conclude that the addition of silicate sol could promote the proliferation of MG-63 cells. The cell morphology changes and improved proliferation capacity can be mainly ascribed to two reasons: the calcium-dependent regulation and the highly enhanced hydrophilicity provided by the presence of the inorganic phase.…”
Section: Resultsmentioning
confidence: 95%
“…However, on day 7, more cells were found on P5B1 scaffold and the majority of cells on P5B1 presented multipolar polygonal morphologies (stellate) with short filopodia, whereas cells on P1B0 still showed bipolar spindle morphologies with relatively long filopodia. Stellate cells can firmly attach, spread and eventually proliferate well on the matrix, whereas bipolar spindle cells are still migrating to locate sites for subsequent spreading and proliferation . Thus, it is reasonable to conclude that the addition of silicate sol could promote the proliferation of MG-63 cells.…”
Section: Results and Discussionmentioning
confidence: 98%
“…These transmembrane proteins can interact with the ECM, directly or indirectly regulate the proliferation of stem cells, and promote cell adhesion and multidirectional differentiation (Abdal Dayem et al, 2018). Some related studies have shown that the micro-nanomorphology of the scaffold surface can affect the adsorption level of cells (Acevedo-Morantes et al, 2012;. Geng et al (2020a) simulated a continuous deep pit-like surface structure inside the gill cover of a snail on the surface of a titanium implant to increase the adsorption level of cells.…”
Section: Cell Adhesion Mechanismmentioning
confidence: 99%
“…These transmembrane proteins can interact with the ECM, directly or indirectly regulate the proliferation of stem cells, and promote cell adhesion and multidirectional differentiation ( Abdal Dayem et al, 2018 ). Some related studies have shown that the micro-nanomorphology of the scaffold surface can affect the adsorption level of cells ( Acevedo-Morantes et al, 2012 ; Li H. et al, 2021 ). Geng et al (2020a) simulated a continuous deep pit-like surface structure inside the gill cover of a snail on the surface of a titanium implant to increase the adsorption level of cells.…”
Section: Mechanism Of Scaffold Structure Promoting Osteogenesismentioning
confidence: 99%